Breastfeeding Knowledge and Behavior in Lactational Amenorrhea Method (LAM) as a Natural Contraceptive - Mufdlilah, Mufdlilah; Johan, Reza Bintangdari; Ningsih, Sri Ratna (Kesmas, 2021)
The lactational amenorrhea method (LAM) is a natural contraceptive that is highly effective after the three essential criteria are fulfilled. However, there is a significantly low adoption resulting from poor knowledge and correct practices. This study aimed to determine the correlation between knowledge and behavior of breastfeeding mothers on breastfeeding as a natural contraceptive. This was an analytic observational study with a cross-sectional design involving 89 breastfeeding mothers and was performed from January to March 2018. Furthermore, data were collected using a questionnaire, and the results showed knowledge of breastfeeding mothers to be good (59.6%) and not good (51.7%). However, the individual’s behavior towards the implementation of LAM was not good (48.3%) and good (40.4%). Based on the statistical test, there was a correlation between knowledge and behavior of breastfeeding mothers, with a p-value of 0.006 (OR = 3.463; 95% CI = 1.411 – 8.498). In brief, knowledge of LAM amongst the participants is good, despite the poor application in terms of behavior. Also, a relationship was also established between the knowledge and behavior of breastfeeding mothers as a natural contraceptive.